A compact, dual-zone vertical tube furnace for the determination of tritium and carbon-14 in decommissioning wastes. (January 2022) - Warwick, Phillip E.; Croudace, Ian W.; Burrell, Frances M.
Abstract: A compact dual zone, two work-tube, vertical tube furnace system (Raddec Pyrolyser-Mini) has been designed for the determination of H-3 and C-14 in decommissioning wastes. An optimised methodology was developed following improvements to sample holder and bubbler trap design, sample loading and loading temperature, as well as length and style of heating programmes. A significant efficiency enhancement was obtained through 'hot-loading' of the sample into the furnace at 600 °C before finally ramping to 900 °C. Direct trapping of H-3 and C-14 in a scintillation vial located in a special anti-suck-back bubbler further improved operations, leading to a reduction in analysis time and measurement sensitivity. Co-trapping of the analytes and dual-label liquid scintillation counting also proved effective. Overall, the developed methodology led to a reduced analyte extraction/trapping time of 150 min whilst achieving limits of detection of <1 Bq/g. Validation of the procedure was assessed using a range of spiked matrices relevant to nuclear site decommissioning, reference materials and operationally-exposed materials. The compact size of this thermal extraction system is such that it allows for deployment in fume cupboards, gloveboxes and a mobile laboratory. Highlights: Novel two-zone vertical tube furnace system for the extraction of H-3 and C-14. Improved sample processing efficiency through hot-loading of samples. Direct trapping of analytes in scintillation vial (including analyte co-trapping). Validated using materials relevant to nuclear site decommissioning. Compact size allowing for on-site deployment or fumecupboard/glovebox operations.